Implementation of The Discovery Learning Model to Improve The Activity and Learning Outcomes - Syarifa Nadira; Maria Erna; Herdini Herdini (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study used classroom action Research to improve student learning activities and outcomes on buffer solutions for Grade XI 1 at SMAN 6 Pekanbaru through discovery learning. The model was applied through stages of stimulation, problem statement, data collection, data processing, verification, and generalization. CAR cycles of planning, action, observation, and reflection addressed learning problems arising from the abstract and microscopic nature of buffer concepts. Participants were 36 students of class XI 1. Results show student learning activities increased from 57.61% (Cycle I, adequate) to 71.10% (Cycle II, good), meeting the success criterion. Student learning outcomes similarly improved, with classical mastery rising from 63.88% in Cycle I to 94.44% in Cycle II, and mean scores increasing accordingly. Findings indicate that systematically implemented discovery learning, supported by teacher scaffolding and iterative refinement, effectively enhances both engagement and achievement in buffer solution topics. The study recommends broader application and further Research on scaffolded discovery approaches across classes.